The Barletta Colossos revisited. - Kiilerich, Bente (Acta ad archaeologiam et artium historiam pertinentia, 2018)
The Barletta colossus is the sole large-scale statue in bronze preserved of a late antique emperor; the only comparable image is the even larger, but fragmentary, Constantinian emperor in Rome. According to local tradition, the Barletta colossus depicts the Byzantine emperor Heraclius (610-641). Modern researchers tend to regard this attribution as mere folklore and fiction. But while there is a general consensus that the statue does not portray Heraclius, there is no agreement as to whom it may have been intended to portray. About a dozen different emperors have been proposed, suggested dates ranging from the fourth to the eighth century. The present article reviews the evidence and discusses the methodological problems we face when dealing with this enigmatic work.